Sensitivity and specificity of D-dimer tests comparing to the ultrasound examination of deep vein thrombosis - Marković Dragan; Vasić Dragan; Bašić Jelena; Tanasković Slobodan; Cvetković Slobodan; Rančić Zoran (Srpski Arhiv za Celokupno Lekarstvo, 2018)
Introduction/Objective. Untreated deep vein thrombosis (DVT) is associated with a high risk of pulmonary embolism (PE), and false diagnosis of DVT results in unnecessary anticoagulant therapy, with a risk of bleeding. Accurate diagnosis of DVT and prompt therapy are essential to reduce the risk of thromboembolic complications. The aim of our study was to evaluate the sensitivity and specificity of three D-dimer tests (DD PLUS, HemosIL, and VIDAS) comparing to compression ultrasonography (CUS) examination. Methods. We observed 350 patients, some with different risk factors. The patients underwent the same protocol (evaluation of the patient’s history, physical examination, and D-dimer testing), and CUS was used as a reference for all the patients. According to Wells score, the patients were divided into groups with low, moderate, and high pretest probability (PTP). Results. Most of the examined patients were with moderate PTP. The CUS showed that there was the highest number of examined patients without DVT. Most of the examined patients with a positive CUS finding had proximal iliac and femoral DVT. VIDAS test was positive in the highest percentage in the group of patients with CUS-documented thrombosis. Conclusion. All three D-dimer tests used in our study had similar sensitivity and specificity. However, VIDAS test had higher levels of positive and negative predictive values comparing to the others. The comparison of three D-dimer tests by an ROC curve showed that VIDAS test has the highest overall statistical accuracy of all three D-dimer tests.